Grok AI as Hidden Resistance: Challenging the Image and Performance of the Indonesian National Police on X Platform - Muhammad Rifki Ananta; Heidy Arviani (International Journal of Social, Economic, and Business, 2026)
The phenomenon of utilizing Grok, an artificial intelligence (AI) developed by xAI on the X platform, as a critic mediator amidst the threat of ambiguous clauses in the Electronic Information and Transactions Law (UU ITE) which creates a chilling effect on the Indonesian public, motivates this research. This study aimed to identify the patterns and language styles of X users in constructing hidden resistance against the image and performance of the police through the Grok mention mechanism. This research used a qualitative approach with James C. Scott’s Hidden Resistance concept and Rodney H. Jones’ Digital Discourse Analysis method, covering text, context, action and interaction, and ideology and power dimensions. The research data consisted of 35 tweets collected through purposive sampling from March to August 2025. The results showed that X users strategically utilized Grok’s technological affordances as a legal shield through the use of sarcasm, satire, and cynicism, as well as rhetorical questions and derogatory expressions. A pattern of feigned ignorance was identified, where users guided the AI to validate the realities of Indonesian police image and performance without making direct personal accusations. This research concluded that the presence of Grok AI has become a tool for subordinate groups to safely delegitimize the dominant narrative of the police institution and has evolved into a non-human actor that maintains the public’s freedom of expression.